Comparison of recent pivotal recommendations for the diagnosis and treatment of late-onset Pompe disease using diagnostic nodes—the Pompe disease burden scale - Hundsberger, Thomas; Schoser, Benedikt; Leupold, Daniela; Rösler, Kai Michael; Putora, Paul Martin (Journal of neurology, 2019)
Pompe disease is a rare autosomal-recessive disorder characterised by limb-girdle myopathy and respiratory weakness in the late-onset form (LOPD). Various mutations in the acid alpha-glucosidase gene lead to toxic lysosomal and extra-lysosomal glycogen accumulation in all organs due to ineffective glycogen clearance by the encoded enzyme. Only one randomized trial demonstrated beneficial effects of respiratory function and meters walked in the 6-min walking test with enzyme replacement therapy (ERT). These results were confirmed in several retrospective and prospective observations and in meta-analyses. Due to a potential lifelong therapy, moderate efficacy and high treatment costs time of ERT initiation and cessation is an ongoing matter of debate. So far, several national and international recommendations have been published with different criteria concerning diagnosis, initiation and cessation of ERT in LOPD. We therefore formally analysed recent published recommendations and consensus statements of LOPD using diagnostic nodes (DODES) as a special software tool. With DODES, an objective analysis becomes possible if the content of the recommendations is represented as algorithms using cross-compatible elements. This analysis formally disclosed both, areas of great heterogeneity and concordance for the diagnosis and management of LOPD and paved the way for a Pompe disease burden scale focussing on ERT initiation. According to this investigation further clinical research should concentrate on ERT in pre-symptomatic and severely affected LOPD patients and on cessation criteria for ERT as these issues are areas of international uncertainty and discordance.